Identification of disulfiram as a secretase-modulating compound with beneficial effects on Alzheimer’s disease hallmarks - Reinhardt, Sven; Kiefer, Falk (Scientific reports, 2018)
ADAM10 is a metalloproteinase acting on the amyloid precursor protein (APP) as an alpha-secretase in neurons. Its enzymatic activity results in secretion of a neuroprotective APP cleavage product (sAPP-alpha) and prevents formation of the amyloidogenic A-beta peptides, major hallmarks of Alzheimer’s disease (AD). Elevated ADAM10 levels appeared to contribute to attenuation of A-beta-plaque formation and learning and memory deficits in AD mouse models. Therefore, it has been assumed that ADAM10 might represent a valuable target in AD therapy. Here we screened a FDA-approved drug library and identified disulfiram as a novel ADAM10 gene expression enhancer. Disulfiram increased ADAM10 production as well as sAPP-alpha in SH-SY5Y human neuronal cells and additionally prevented A-beta aggregation in an in vitro assay in a dose-dependent fashion. In addition, acute disulfiram treatment of Alzheimer model mice induced ADAM10 expression in peripheral blood cells, reduced plaque-burden in the dentate gyrus and ameliorated behavioral deficits. Alcohol-dependent patients are subjected to disulfiram-treatment to discourage alcohol-consumption. In such patients, enhancement of ADAM10 by disulfiram-treatment was demonstrated in peripheral blood cells. Our data suggest that disulfiram could be repurposed as an ADAM10 enhancer and AD therapeutic. However, efficacy and safety has to be analyzed in Alzheimer patients in the future.
Gesehen am 19.09.2019